(untitled) (Journal of Informatics Education and Research, 2026)
This paper discusses how human resource training and development programs influence supply chain integration and coordination, highlighting the need to explore how human capital initiatives lead to effective supply chain operations. A quantitative and cross-sectional research design was adopted, with a focus on primary data collected through a structured questionnaire administered to employees in human resource, operations, and supply chain positions across manufacturing and service organizations. Descriptive statistics, reliability analysis, correlation analysis, multiple regression analysis, and Structural Equation Modeling were used to conduct the data analysis. The outcomes show that HR training and development programs are significantly and positively related to supply chain integration (r = 0.62) and coordination (r = 0.58). The regression analysis indicates that training initiatives can explain about 29 percent of the variance in supply chain integration. Structural modeling also indicates that supply chain integration plays an important role in improving coordination (beta = 0.61), which demonstrates its mediating nature. The results indicate that effective training and development interventions reinforce inter-organizational teamwork and coordination among supply chain activities, which ultimately enhances coordination. The research concludes that investing in employee development is a strategic process for enhancing the performance of an integrated and coordinated supply chain.